a rectangle has a perimeter of 46cm and an area of 120cm squared. find its dimensions by writing an equation and using the quadratic formula to solve it. Thanks!

Answers

Answer 1
Answer: Let length = l , width = b
Perimeter = 2 (l +b)
46= 2 (l +b)
(l + b) = 23

l*b = 120

So l + 120/l = 23
l^2 + 120 - 23l = 0
l^2 -15l + 8l + 120 = 0
(l-8) (l - 15) = 
l = 8 or 15
i.e if l =8, w=15 
and if l = 15, w = 8

Related Questions

Help plz Character limit = EEEEEEEEEEEEEEEEE
A Greenhouse has the shape of a cylinder and rectangular prism, as show. In order to air condition the building the owner needs to know the volume of the empty green house. What is the volume, in cubic feet? leave your answer to the nearest hundredths.Volume Cylinder= _______cubic feet Volume total= ______cubic feet
Translate the following statement into a mathematical equation:Six, plus four times a number, is eighteen. (6 + 4)n = 18 4n + 18 = 6 6 + 4n = 18 6 + 4 + n = 18
A stadium has 45,000 seats. Seats sell for ​$30 in Section​ A, ​$24 in Section​ B, and ​$18 in Section C. The number of seats in Section A equals the total number of seats in Sections B and C. Suppose the stadium takes in ​$1,168,800 from each​ sold-out event. How many seats does each section​ hold?
Can someone please help me with Geometry?

Evaluate the polynomial 6x - y for x = 3 and y =4

Answers

6 x 3 is 18.  y is equal to 4.  18 minus 4 is 14.  The answer is 14.

Use Gauss-Jordan elimination to solve the following linear system.x – 6y – 3z = 4
–2x – 3z = –8
–2x + 2y – 3z = –14

Answers

\begin{cases}x-6y-3z=4&(1)\n-2x-3z=-8&(2)\n-2x+2y-3z=-14&(3)\end{cases}

First eliminate y by adding (1) to three times (3). This gives

(x-6y-3z)+3(-2x+2y-3z)=4+3(-14)\iff -5x-12z=-38

This reduces the system of one of two equations and two unknowns:

\begin{cases}-5x-12z=-38&(1)^*\n-2x-3z=-8&(2)^*\end{cases}

You can eliminate z by subtracting (1)^* and four times (2)^* to get

(-5x-12z)-4(-2x-3z)=-38-4(-8)\iff3x=-6\implies x=-2

Back-substitute to find z and y. You should end up with (x,y,z)=(-2,-3,4).

Answer:

(-2,-3,4)

Step-by-step explanation:

A quadratic equation is shown below:x2 − 8x + 13 = 0

Which of the following is the first correct step to write the above equation in the form (x − p)2 = q, where p and q are integers?
Subtract 5 from both sides of the equation

Add 3 to both sides of the equation

Add 5 to both sides of the equation

Subtract 3 from both sides of the equation

Answers

The given quadratic equation can be represented in the form (x-p)^2 = q

by adding 3 to both sides of the equation.

What is a quadratic equation?

The polynomial equation whose highest degree is two is called a quadratic equation. The equation is given by

ax^2 + bx + c = 0

where a\neq 0.

The given quadratic equation is

x^2 - 8x + 13 = 0

Case 1: Subtract 5 from both sides of the equation

i.e.  x^2 - 8x + 13 - 5 = 0 - 5

⇒   x^2 - 8x + 8 = -5

The LHS of the above equation can not be expressed in (x-p)^2 form. Hence, it is not the correct step.

Case 2: Add 3 to both sides of the equation.

i.e. x^2 - 8x + 13 +3 = 0 + 3

⇒  x^2 - 8x + 16 = 3

⇒  x^2 - 2* x * 4 + (4)^2 =3

⇒  (x - 4)^2 = 3

The above equation is expressed in (x-p)^2 = q form where p = 4 and q = 3.

Case 3: Add 5 to both sides of the equation

i.e. x^2 - 8x + 13 + 5 = 0+5

⇒   x^2 - 8x + 18 = 5

The LHS of the above equation can not be expressed in the (x-p)^2. Hence, it is not the correct step.

Case 4: Subtract 3 from both sides of the equation

i.e. x^2 - 8x + 13 - 3 = 0-3

⇒   x^2 - 8x + 10 = -3

The LHS of the above equation can not be expressed in the (x-p)^2. Hence, it is not the correct step.

Hence, "Add 3 to both sides of the equation" is the correct step.

Learn more about quadratic equations here:

brainly.com/question/2263981?referrer=searchResults

#SPJ2

Add 3 to both sides, so you will have

x^2 - 8x + 13 + 3 = 3
x^2 -8x + 16 = 3

And now the left side is a perfect square trinolmial: (x-4)^2.

the ratio of the circumferences of two circles is 2:3. If the large circle has a radius of 39 cm, what is the radiusof the small circle?

Answers

Answer:

r_(1) = 26.

Step-by-step explanation:

Given : the ratio of the circumferences of two circles is 2:3. If the large circle has a radius of 39 cm,

To find : what is the radius of the small circle.

Solution : We have given that ratio of the circumferences of two circles is 2:3.

Let r_(2)  is radius of larger circle and  r_(1)  is radius of small circle .

Then circumference = (2\pi\ r_(1) )/(2\pi\ r_(2)) = (2)/(3) .

Solving the above equation

(r_(1))/(r_(2) ) =  (2)/(3) .

We have given radius of larger circle = 39 then

(r_(1))/(39) =  (2)/(3) .

On multiplying both sides by 39.

r_(1) = 39 *(2)/(3).

r_(1) = 13 * 2.

r_(1) = 26.

Therefore, r_(1) = 26.

C1/C2 =  2/3

 2pi r1 / 2pi r2 = r1/r2 = 2/3

r1/39 = 2/3

r1 = 39*2/3 = 26

So, your answer is 26cm

The first order was 13 bushes and 4 trees for a total of $487 the second order was 6 bushes and 2 trees for a total of $232 what were the costs of one bush and of one tree

Answers

Hagan asks a jowksbsbs lwks962

Can someone also help me simplify 5(–2xy)

Answers

Answer:

-10xy

Step-by-step explanation:

distributive property

5*-2=-10

-10xy

Answer:

-10xy

Step-by-step explanation: